Effect of electroslag remelting on the non-metallic inclusions in H11 tool steel - Burja J.; Tehovnik F.; Godec M.; Medved J.; Podgornik B.; Barbič R. (Journal of Mining and Metallurgy. Section B: Metallurgy)
We have studied the effect of electroslag remelting on the content and composition of non-metallic inclusions. It was found that a decrease in the non-metallic inclusion content occurred during the electroslag remelting. A change in the chemical composition of the non-metallic inclusions was observed, while the aluminum and calcium contents were increased. The complexity of the inclusions also increased, as there were fewer single-phase inclusions after the electroslag remelting process. Based on the results and a thermodynamic assessment of the formation of the non-metallic inclusions, a mechanism for inclusion behavior during electroslag remelting has been proposed.